Measuring human performance using annual work target evaluation system - Noraziah, Ahmad; A. M., Abang Fairul Syarmil; Herawan, Tutut; Munira, Abdul Razak (Elsevier Ltd., 2011)
Nowadays, high or upper level of some business and operative management need to know how the performance of the staff. In addition, the human performances can be measured through its quantitative elements in order to obtain its qualitative measurement. Annual Work Target Evaluation System (AWTES) is a system that can be used to measure the human performance, thus an organization's target in some area of its business can be monitored too. Currently, Faculty of Computer System & Software Engineering (FCSSE) deploys a system where it can evaluate the performance of the staff. However, the higher level management cannot view the progress on the results in more effective ways such as via the graph or chart. Therefore, the development of AWTES is necessary to predict and monitor the organization performance using generated graph so that their performance are more effective to be view by the high level management. The methodology that is implied in the project development is the Iterative and Incremental Development Methodologies. This prototype has 6 modules and able to evaluate the performance based on quantitative elements which can be set by the user. AWTES is developed by using the Adobe Dreamweaver CS4 and NetServer. By using AWTES, it helps the management of the department to know the performance of their staff and furthermore improves an organization performance.